The Horseback Librarians - Yolen, Jane; Badiu, Alexandra (Chicago, Illinois : Albert Whitman & Company, 2023)
"In 1930's rural Kentucky, Anna Mary, rhymes with library, and her horse, Sand, go from farm to farm to deliver books to the delight of both children and adults"--
Keywords: Packhorse librarians -- Juvenile fiction; Books and reading -- Juvenile fiction; Packhorse librarians -- Fiction; Books and reading -- Fiction; Kentucky -- Fiction; Kentucky -- Juvenile fiction; Picture books